Effects of Mindfulness Training on Emotion Regulation in Patients With Depression: Reduced Dorsolateral Prefrontal Cortex Activation Indexes Early Beneficial Changes. Issue 6 (July 2021) - Barnhofer, Thorsten; Reess, Tim J.; Fissler, Maria; Winnebeck, Emilia; Grimm, Simone; Gärtner, Matti; Fan, Yan; Huntenburg, Julia M.; Schroeter, Titus A.; Gummersbach, Marie; Bajbouj, Malek; Hölzel, Britta K.
ABSTRACT: Objective: Mindfulness-based interventions (MBIs) have been found to be a promising approach for the treatment of recurrent courses of depression. However, little is known about their neural mechanisms. This functional magnetic resonance imaging study set out to investigate activation changes in corticolimbic regions during implicit emotion regulation. Methods: Depressed patients with a recurrent lifetime history were randomized to receive a 2-week MBI ( n = 16 completers) or psychoeducation and resting (PER; n = 22 completers). Before and after, patients underwent functional magnetic resonance imaging while labeling the affect of angry, happy, and neutral facial expressions and completed questionnaires assessing ruminative brooding, the ability to decenter from such thinking, and depressive symptoms. Results: Activation decreased in the right dorsolateral prefrontal cortex (dlPFC) in response to angry faces after MBI ( p < .01, voxel-wise family-wise error rate correction, T > 3.282; 56 mm 3 ; Montreal Neurological Institute peak coordinate: 32, 24, 40), but not after PER. This change was highly correlated with increased decentring ( r = −0.52, p = .033), decreased brooding ( r = 0.60, p = .010), and decreased symptoms ( r = 0.82, p = .005). Amygdala activation in response to happy faces decreased after PER ( p < .01, family-wise error rate corrected; 392 mm 3 ; Montreal Neurological Institute peak coordinate: 28, −4, −16), whereas the MBI group showed no significant change. Conclusions: The dlPFC is involved in emotion regulation, namely, reappraisal or suppression of negative emotions. Decreased right dlPFC activation might indicate that, after the MBI, patients abstained from engaging in elaboration or suppression of negative affective stimuli; a putatively important mechanism for preventing the escalation of negative mood. Trial Registration: The study is registered at ClinicalTrials.gov (NCT02801513; 16/06/2016). Abstract : Supplemental digital content is available in the text.